Second law based performance analysis of seawater source cascade heat pump system: a case study. (4th March 2010) - Tyagi, S.K.; Anand, S.; Park, S.R.; Tyagi, V.V.
This paper presents the second law based analysis of a seawater source cascade heat pump system operating with two different refrigerants. The present cascade heat pump system consists of two different heat pumps attached in such a way that the condenser of the first stage heat pump is the evaporator for the second heat pump and the condenser of the second heat pump is attached to the place to be heated. The rate of irreversibility for the low pressure compressor is found to be higher than that of the high pressure compressor.